Hubungan antara Konsep Diri dengan Depresi pada Transgender: Kajian Literatur - Salsabila Nur Istigfari; Elis Hartati (Holistic Nursing and Health Science, 2021)
Introduction: Transgenders have a high risk of depression caused by self-concept. the complex aspect of self-concept has led to different results among researchers in examining the relationship between self-concept and depression experienced by transgender. The purpose of this study was to strengthen evidence on the relationship between self-concept and depression in transgender.Method: This study uses a literature review method. Articles searched through Google Scholar, Cambridge, Clinical Key, NCBI, MDPI, and Science Direct. Articles were selected based on several criteria including: research with a minimum sample of 15 transgender, publication year 2011-2020, written in Indonesian or English, and full text articles. Quality assessment as a method to assess the relevance of the journals. Results: Eleven articles were selected based on the sample criteria, but only 7 articles were relevant to be reviewed. The results of the synthesis show that there is a relationship between self-concept and depression in transgender people. The level of depression in transgender is influenced by several factors, including: lack of social support, low self-esteem, body image dissatisfaction, lack of coping skills, social and emotional loneliness, and low sexual satisfaction.Conclusion: There is a significant relationship between self-concept and depression in transgender people, but there is no strong evidence that proves the influence of organizational involvement on self-concept in transgender.